Falling Standard of education in Pakistan: Who will tie the bell? - Muhammad Afzal; Fazli Qadir (PT ARRUS Intelektual Indonesia, 2022)
The paper investigated and analysed the various factors assumed to be responsible for falling quality of education and the necessary data were collected from university students whom were asked relevant questions. Students expressed dissatisfaction on the semester system and BS program. BS program has killed the students because they are bogged down in the vicious circle of plethora of courses which not only affect their health but also their academic performance. MPhil and PhD admissions are reduced to minimum in the light of demand and supply to avert future problems.The most deplorable aspect is TTS which is supposed to have done more harm and damage to the national exchequer than alleged good. Lecturers in universities enjoy the lucrative BPS-18 scale while doctors, engineers, civil servants are inducted in BPS-17. Step-motherly treatment of other civil servants will certainly add to bad blood. TTS and induction in BPS-18 as lecturer must be stopped once for all. Lack of job opportunities and rapid population growth are potential factors responsible for falling standard of education. When students are aware that their hard labour will not bear fruit, they lose interest in working hard. Social media has added fuel to the fire.